The Effect of Probiotic Administration (Yogurt) on the Incidence of Constipation in Pregnant Women in the Third Period in the Bolaang Mongondow Pusian Community Health Center Work Area - Susisusanti Yohanis; Widia Shofa Ilmiah (NAJ Nursing Applied Journal, 2025)
Constipation is a common gastrointestinal complaint among pregnant women, particularly during the third trimester, due to hormonal changes, reduced intestinal motility, and mechanical pressure from the enlarged uterus. This condition can negatively affect maternal comfort and quality of life. Probiotics have been suggested as a safe, non-pharmacological intervention to improve bowel function during pregnancy. This study aimed to analyze the effect of probiotic (yogurt) administration on constipation among third-trimester pregnant women in the working area of Puskesmas Pusian, Bolaang Mongondow Regency. A quantitative study with a quasi-experimental design was conducted involving 40 third-trimester pregnant women selected through purposive sampling. Respondents were divided into two groups: those who received probiotic yogurt and those who did not. Constipation was assessed using the Bristol Stool Scale. Data were analyzed using univariate analysis and bivariate analysis with the Mann–Whitney U test. The results showed a statistically significant difference in constipation outcomes between the probiotic and non-probiotic groups (p = 0.000). Pregnant women who received probiotics demonstrated better stool consistency and bowel movement patterns compared to those who did not receive probiotics. In conclusion, probiotic yogurt administration has a significant effect in reducing constipation among third-trimester pregnant women and can be recommended as a safe and practical intervention in antenatal care services.